Foreign body reaction to a retained surgical sponge (gossypiboma) mimicking an implant associated sarcoma in a dog after a tibial plateau levelling osteotomy - Corbin, E. E.; Cavanaugh, R. P.; Fick, J. L.; McAbee, K. P.; Powers, B. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
A dog was presented with the complaint of an acute onset left pelvic limb lameness three years after a right tibial plateau levelling osteotomy had been performed. Radiographs taken at the time of presentation showed signs that were consistent with a diagnosis of an implant associated sarcoma. At revision surgery, a retained surgical sponge was identified, leading to a diagnosis of a gossypiboma. This is the first reported case of a gossypiboma as a complication of a tibial plateau levelling osteotomy surgery.
Keywords: Gossypiboma; textiloma; tibial plateau levelling osteotomy; implant associated sarcoma; TPLO